CIBERCITIZENSHIP AND CIBERDEMOCACY: VIRTUAL COMMUNITIES AND THE INFLUENCE OF MASSES BY TIC'S. (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This study aims to investigate the impacts and the level of influence of the technological means of communication, especially the virtual communities formed in social networks, for the exercise of citizenship and democratic popular participation. In this context, the clarification of the concepts of cyber citizenship and cyberdemocracy, which are necessary to delineate the favorable and unfavorable arguments of mass control by ICT (Information and Communication Technologies). The path followed goes through the development of the internet and the globalization of connectivity, to then reach the present moment, when social media are developing as determining tools for the dominance and imposition of opinions formed in social networks, including those based on fake news to, to conclude, what are the consequences of the telematic means of communication in the affirmation of the rights and duties of the Brazilian citizens. To this end, we apply the deductive approach method, in conjunction with the bibliographic research technique, through doctrinal analysis on the subject.